2015
DOI: 10.1007/s12028-015-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Predicts Neurogenic Pulmonary Edema in Patients with Subarachnoid Hemorrhage

Abstract: Loss of cardiac variability and depressed sympathovagal modulation, represented by TP and LF %, may predict the development of NPE in the early stage in patients with SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
17
0
3
Order By: Relevance
“…A few very interesting randomized trials are currently investigating neurocritical care measures beyond neurosurgery in or including SAH: EARLYDRAIN on early lumbar drainage combined with EVD [9], SETPOINT2 on early tracheostomy [10], NEWTON on slow-release nimodipine via EVD [11], ULTRA on early tranexamic acid [12], and HIMALAIA on induced hypertension [13]. However, there are so many other NCCU aspects to be addressed prospectively: level of sedation, modes of ventilation [14,15], cardiopulmonary stability [16,17], monitoring-based circulatory strategies [18], temperature control [19][20][21], delirium management, the nursing factor and mobilization, policies of do-not-resuscitate orders and withdrawal of care [22,23], and many other day-to-day care decisions that may substantially impact outcome. Particularly, the poor-grade SAH patient, prone to so many cerebral and systemic complications, may benefit from aggressive surveillance, superb nursing care, and close clinical monitoring.…”
mentioning
confidence: 99%
“…A few very interesting randomized trials are currently investigating neurocritical care measures beyond neurosurgery in or including SAH: EARLYDRAIN on early lumbar drainage combined with EVD [9], SETPOINT2 on early tracheostomy [10], NEWTON on slow-release nimodipine via EVD [11], ULTRA on early tranexamic acid [12], and HIMALAIA on induced hypertension [13]. However, there are so many other NCCU aspects to be addressed prospectively: level of sedation, modes of ventilation [14,15], cardiopulmonary stability [16,17], monitoring-based circulatory strategies [18], temperature control [19][20][21], delirium management, the nursing factor and mobilization, policies of do-not-resuscitate orders and withdrawal of care [22,23], and many other day-to-day care decisions that may substantially impact outcome. Particularly, the poor-grade SAH patient, prone to so many cerebral and systemic complications, may benefit from aggressive surveillance, superb nursing care, and close clinical monitoring.…”
mentioning
confidence: 99%
“…NPE secondary to neurocritical injuries has an estimated incidence ranging between 2% and 50%, and it occurs more often in patients with severe TBI than in those with SAH. [ 1 , 48 ] Based on the mechanism of NPE related to sympathetic nervous activity, Chen et al [ 49 ] examined heart function in 204 patients with SAH and found that heart rate variability can predict the occurrence of NPE.…”
Section: Pulmonary Complications In Nccmentioning
confidence: 99%
“…[4,[11][12][13] Penelitian yang dilakukan oleh Chen et al 2015 di Taiwan menunjukan bradikardia pada pasien SAH akan memberi prognosis buruk NPE. [14] Dari 20 pasien SAH dan NPE di taiwan hanya 1 pasien saja yang bisa melanjutkan kehidupan. [13] Huang et al pada tahun 2016 melakukan penelitian yang mencari hubungan gambaran abnormalitas dalam memprediksi insidensi NPE, dalam penelitian tersebut terdapat hubungan antara abnormalitas gambaran EKG pada pasien dengan NPE.…”
Section: Artikel Tinjauan Pustakaunclassified